POLA BAKTERI DAN RESISTENSI ANTIBIOTIK PADA ULKUS DIABETIK GRADE DUA DI RSUD ARIFIN ACHMAD PERIODE 2012 - Galuh Tiara Akbar; Jazil Karimi; Dewi Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Diabetic ulcer is chronic complication of diabetes melitus shown as connective tissues ulceration and destruction on lower limbs caused by uncontrollable hyperglycaemic of Diabetes melitus patient that lead into peripheral angiopathy and neuropathy so that bacterial infection trauma will easily occur. This research’s goal is to find out bacterial pattern and antibiotic resistance of second grade diabetic ulcer patients that have been hospitalized in General Hospital Arifin Achmad on 2012. 23 comprehensive medical records have been used in this descriptive and retrospective methode of research. From distribution of age category has been found 40-59 years old as the highest percentage (87%). Based on gender has been found female respondents (78,3%) and male respondents (21,7%). Most of patients have been suffered Diabetes melitus for less than 5 years (60,9%) and allowed to went home after treatment (82,6%). Most commonly bacteria that found based on bacterial culture and resistance test was Acinetobacter baumanii (34,8%), Klebsiella pneumoniae (26,2%) and Escherichia coli (17,4%). Amoxicillin and ampicillin have lowest sensitivity (0%), followed by trimethoprim/sulfametoxazole (17,4%) and cefotaxime as well as ciprofloxacin was 21,7%. The highest sensitivity antibiotics was meropenem (100%), imipenem, amikacin, and colistin (95,6%), followed by ertapenem (91,3%).Keywords: diabetic ulcer, bacterial pattern, resistance test, sensitivity, antibiotic